Two-step quantum secure direct communication scheme with frequency coding - 赵学亮 李俊林 牛鹏皓 马鸿洋 阮东 (Chinese physics B, 2017)
Quantum secure direct communication （QSDC） is an important branch of quantum cryptography. It can transmit secret information directly without establishing a key first, unlike quantum key distribution which requires this precursory event. Here we propose a QSDC scheme by applying the frequency coding technique to the two-step QSDC protocol, which enables the two-step QSDC protocol to work in a noisy environment. We have numerically simulated the performance of the protocol in a noisy channel, and the results show that the scheme is indeed robust against channel noise and loss. We also give an estimate of the channel noise upper bound.